Madrasa Committee Participation in the Implementation of the Integrated Curriculum as an Effort to Strengthen the Profile of Madrasah Aliyah Institutions - Saipul Umar; Agung Gumelar (Progressive of Cognitive and Ability, 2023)
Curriculum planning is the stage of determining goals according to the vision and mission of the madrasa. For this reason, the purpose of this study is to examine the involvement of madrasah committees and the application of an integrated curriculum as an effort to strengthen the character of Islamic-based institutions. This mixed-method research (quantitative-quantitative) took primary data (interviews and questionnaires) and secondary data (documents) at Madrasah Aliyah Darul Huda in MA Darul Huda is one of the educational institutions within the Darul Huda Islamic Boarding School which is located in Sri Menanti Village, Buay Pemaca District, South Ogan Komering Ulu Regency in South Sumatra Province with a one-roof madrasa education model as a formal educational institution. OKU district. The results of the study explain that the role of school committees is very important in the implementation of madrasah education to improve quality and emphasize the character of Islamic educational institutions. Madrasah Aliyah has implemented an integrated curriculum by absorbing the national curriculum with the Islamic boarding school curriculum-based Madrasah curriculum. Teaching materials at MA Darul Huda have been adjusted to the competency standards and basic competencies that exist in the curriculum content standards of the Ministry of Religion. In the process of implementing education, Madrasahs involve madrasah committees, but the committees have not made the maximum contribution to efforts to improve the quality and strengthen the institutional character of Islamic boarding schools, even though the madrasah committees have been heavily involved.